(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present study was designed to formulate and evaluate the Olmesartan sodium alginate microspheres. Fourteen formulations batches of microspheres (S1-S14) were prepared by using ionotropic gelation method. Sodium alginate, calcium chloride, ethyl cellulose, HPMC K15M was selected in the formulations. The effect of polymer and cross-linking agent on particle size (68.18 ± 0.06), % yield (98.34%), entrapment efficiency (97.36%), and drug release were studied. From the evaluation parameters S11 was found to be optimized and the highest drug release 96.98 ± 5.28 with in 12 h in controlled manner when compared with other parameters. From release order kinetics the drug release from microspheres was followed zero order with anomalous Non fickian diffusion. The prepared microspheres compatibility studies and morphological studies were investigated by Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM), found to be compatible with the polymers. Thus, Olmesartan microspheres could be the best choice in the effective management of hypertensive with better patient compliance for prolonged period of time.